EFEITO DA CENSURA SOBRE A FUNÇÃO DE INCIDÊNCIA CUMULATIVA NA PRESENÇA DE RISCOS COMPETITIVOS NA ANÁLISE DE SOBREVIVÊNCIA - TOMAZ, Flávia Sílvia Corrêa; MARTINS FILHO, Sebastião (Brazilian Journal of Biometrics, 2019)
The objective of this work was to evaluate the effect of censorship on the estimation of cumulative incidence in the presence of competing risks. For this, sets of survival times with competing risks considering different levels of censorship (0%, 10%, 20%, 30%, 40% and 50%) were simulated. The simulation was based on the cause-specific hazard and the exponential distribution was used. For the simulation of the censorship times, the uniform distribution was used. In addition to the different levels of censorship, different values were considered for the cause-specific hazard in the two simulated competing events. Comparisons between the incidence curves of the uncensored data set and the set with different percentages of censorship were performed. We also compared the estimates of the cumulative incidence function based on the theory of competing risks with that obtained by using the Kaplan-Meier estimator. The results indicate that censorship percentages as well as the relation between cause-specific hazard affect the cumulative incidence.